AN ANALYSIS OF CODE-MIXING USED BY ENGLISH TEACHER IN CLASSROOM INTERACTION AT NINETH GRADE MTS ANAK BANGSA - Nasution, Nabilla Fauza (BRIGHT VISION Journal of Language and Education, 2024)
The research entitled "Analysis of the Use of Code Mix by English Teachers in Classroom Interaction" aims to identify the types of code mixing used by English teacher as well as the reasons behind their use in the teaching process. This research uses descriptive qualitative method, with the research subject being an English teacher at Mts Anak Bangsa. Data were gathered through observation, documentation, and interviews, and then analyzed using techniques for data reduction, data display, and drawing and verifying conclusions, as outlined by Sugiyono. The research findings show that there are three types of code mix used by teachers in classroom interactions, namely intra-sentential code mixing (77.16%), intra-lexical code mixing (12.34%), and involving change of pronunciation (10.50%). Among the three types, intra-sentential code-mixing is the most frequently used. English teachers use code-mixing due to situational factors, intrinsic messages and language attitudes which include dominance and security. The study concludes that teachers' use of code-mixing helps bridge language gaps between teachers and students, thereby enhancing students' comprehension of the subject matter.